2018
DOI: 10.1007/s00436-018-6050-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of raw propolis on Varroa-infested honey bee (Apis mellifera) workers

Abstract: Self-medication plays a major role in the behavioral defense against pathogens and parasites that animals have developed during evolution. The conditions defining this adaptive behavior are: (1) contact with the substance in question must be deliberate; (2) the substance must be detrimental to one or more parasites; (3) the detrimental effect on parasites must lead to increased host fitness. Recent studies have shown that A. mellifera colonies are able to increase resin foraging rates when infested by V. destr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Secondly, we ascertained whether infected bees were more attracted to a diet containing propolis and consumed a greater proportion of this diet in comparison to uninfected bees. Considering that the biological properties of propolis have mainly been associated with its phenolic components [43,[58][59][60], we also quantified the polyphenol content together with the main phenolic compounds of the propolis used in our bioassays.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we ascertained whether infected bees were more attracted to a diet containing propolis and consumed a greater proportion of this diet in comparison to uninfected bees. Considering that the biological properties of propolis have mainly been associated with its phenolic components [43,[58][59][60], we also quantified the polyphenol content together with the main phenolic compounds of the propolis used in our bioassays.…”
Section: Introductionmentioning
confidence: 99%
“…Our results corroborate with those of previous studies in European honey bee colonies, which also reported no significant effects of the natural propolis envelope on mite loads using either our same or larger sample size of six colonies (Borba et al ., 2015; Drescher et al ., 2017). In contrast to this and previous findings, Pusceddu et al found that the quantity of resin collected by the European honey bee, A. mellifera ligustica correlated with the levels of mite infestation (Pusceddu et al ., 2018). These contrasting effects of natural propolis on mite-infestation levels could be a result of the variable chemical composition of the resinous fraction of propolis in the differential geographical areas where these studies were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the bioactive compounds found in the resinous fraction of propolis are both non-volatile given the bath temperature and reduced pressure during rotatory evaporation, and relatively polar since extracted into ethanol. Pusceddu et al (2018) noted narcotic effects on mites exposed to crude propolis samples collected from A. m. ligustica colonies, though as they suggested, these effects were minimal when compared to those caused by the ethanolic extracts of propolis samples collected from other A. mellifera colonies (Garedew et al, 2002;Damiani et al, 2010).…”
mentioning
confidence: 98%
“…For instance, Argentinian propolis was found to be very effective against Varroa [89]. Furthermore, ethanolic extracts of German propolis were highly toxic to Varroa destructor, with a 10% w/v solution being lethal at 5 s contact [90], and Pusceddu et al observed that raw propolis highly significantly increased the lifespan of Varroa-infected bees, almost completely reversing Varroa-associated mortality [91]. Moreover, the addition of natural propolis to hives reduced the titer of Varroa-transmitted deformed wing virus (DWV) [92] and Varroa-infected colonies specifically increased resin foraging [93].…”
Section: Evidence For Propolis Protection Against Bee Infectionsmentioning
confidence: 99%
“…Moreover, the addition of natural propolis to hives reduced the titer of Varroa-transmitted deformed wing virus (DWV) [92] and Varroa-infected colonies specifically increased resin foraging [93]. It is not yet clear which chemical agents in propolis reduce the impact of Varroa infestation, but it was reported that the total polyphenolic content of propolis correlated with levels of Varroa infection in experimental hives in Sardinia [91]. Caffeic acid and pentenyl caffeates were found to be more abundant in propolis from Varroa-susceptible colonies [94], but this association requires further investigation in order to be confirmed as causal.…”
Section: Evidence For Propolis Protection Against Bee Infectionsmentioning
confidence: 99%